Incident cardiovascular disease and particulate matter air pollution in South Korea using a population-based and nationwide cohort of 0.2 million adults - Ok-Jin Kim; Soo Hyun Lee; Si-Hyuck Kang; Sun-Young Kim (BMC, 2020)
Abstract Background While many studies reported the association between long-term exposure to particulate matter air pollution (PM) and cardiovascular disease (CVD), few studies focused on incidence with relatively high-dose exposure using a nationwide cohort. This study aimed to investigate the association between long-term exposure to PM10 and PM2.5 and incidence of CVD in a nationwide and population-based cohort in South Korea where the annual average concentration of PM2.5 is above 20 μg/m3. Methods We selected 196,167 adults in the National Health Insurance Service-National Sample Cohort (NHIS-NSC) constructed based on the entire South Korean population. Incidence of four CVD subtypes including ischemic heart disease (IHD), myocardial infarction, heart failure, and stroke, and total CVD including all four was identified as the first diagnosis for 2007-2015. To assess individual exposures, we used annually-updated district-level residential addresses and district-specific PM concentrations predicted by a previously developed universal kriging prediction model. We computed individual-level long-term PM concentrations for four exposure windows: previous 1, 3, and 5 year(s) and 5 years before baseline. We applied time-dependent Cox proportional hazards models to estimate hazard ratios (HRs) of incident CVDs per 10 μg/m3 increase in PM10 and PM2.5 after adjusting for individual- and area-level characteristics. Results During 1,578,846 person-year, there were 33,580 cases of total incident CVD. Average PM10 and PM2.5 concentrations for the previous 5 years were 52.3 and 28.1 μg/m3, respectively. A 10 μg/m3 increase in PM2.5 exposed for the previous 5 years was associated with 4 and 10% increases in the incidence of total CVD (95% confidence interval: 0-9%) and IHD (4-16%), respectively. HRs tended to be higher with earlier exposure for IHD and more recent exposure for stroke. The estimated shape of the concentration-response relationship showed non-linear patterns. We did not find evidence of the association for PM10. Conclusions Using a population-based nationwide cohort exposed to relatively high PM concentration, this study confirmed the association between PM2.5 and CVD incidence that was reported in previous studies mostly with low-dose environments. The magnitude and the shape of the association were generally consistent with previous findings.